Signal encoding method and device, method for encoding joint feedback signal - Fan, Shuju; Ma, Xueli; Wang, Zongjie; Li, Jing (2017)
A signal encoding method and device and a method for encoding a joint feedback signal are provided. The signal encoding method includes the following steps. When two carriers are configured with multiple-input and multiple-output (MIMO), Hybrid Automatic Repeat reQuest-ACKnowledgement (HARQ-ACK) signals of the two carriers are combined into a joint feedback signal. The joint feedback signal is mapped into a codeword according to predetermined mapping relationship between signals and codewords. Therefore, through the method for combining and encoding feedback signals of two carriers for transmission on a code channel in a dual cell (DC)-MIMO mode, bit error ratio (BER) and detection error cost are decreased, power overhead is saved, and a cubic metric (CM) value of the system is not affected, thereby enhancing the performance of the system.